The challenges of university teaching - Hernández Rodríguez, Ana Cecilia (2011)
This paper presents a reflectionabout the challenges facing university education at the present time, with respect toglobal and national conditions.Globally discusses briefly therelevant problems of an economic, social,scientific and technological development, and the expansion of the university system and funding problems. At the national level, are analyzedfollowing: Linking Universitywith the national education system featuresteaching we do, incorporating educational technology into teaching in higher education, conditions of teachers and students, the management skills to support teaching and public universities versus private universities.From this analysis expresses the need to review, critically, the university work, ofrecover and strengthen the character of "clear consciousness," to seek, steadily overcomingrenew academic and pedagogic practice.